Multi Objective Optimization of Turning AISI 4340 Steel Considering Spindle Vibration Using Taguchi- Fuzzy Inference System. (2015) - Kamble, Prashant D.; Waghmare, Atul C.; Askhedkar, Ramesh D.; Sahare, Shilpa B.
Abstract: Multi-objective: optimization (MOO) of cutting parameters for turning AISI 4340 steel is experimentally investigated by applying fuzzy logicwith Taguchi method. The effect of uncontrollable parameter (spindle vibration) along with the controllable parameters on multiple objectives is studied. Use of uncontrollable factor helped to make the design robust. Coated and un-coated cutting tools and the latest lubrication method (Minimum quantity lubrication) are also considered to match the current scenario of manufacturing system. Fuzzy logic is used to change multiple objectives to a single objective. Regression model is developed for multiple objectives. The data analysis concealed the optimal setting for turning process.